Internalization of the Thin-Ideal and Eating Pathology in Kuwaiti Adult Women - Zainal, Lulwa; Stevens, Serena D.; Harriger, Jennifer Ann; Herbozo, Sylvia (Frontiers in Psychology, 2020)
Rapid socioeconomic growth, Western acculturation, and thin ideal internalization are theorized to be linked to dieting, weight concerns, and disordered eating in Arab countries. The purpose of this study was to examine eating pathology and the internalization of Western messages regarding the importance of thinness in a community sample of Kuwaiti women. Participants (N= 83) aged 18-35 years with BMIs between 17.58 and 24.88 (M = 21.30; SD = 1.83) completed measures of thin-ideal internalization and eating pathology. Results demonstrated that approximately 28% of the sample were at risk for eating pathology. Thin-ideal internalization was also found to significantly predict eating pathology. Study findings extend prior research on eating pathology in Arabic nations. This study is the first to examine the internalization of the thin ideal in a community sample of Kuwait adult women and lends further support to the importance of continued research in this population.